The Effect of Microplastics on the Bioenergetics of the Mussel Mytilus coruscus Assessed by Cellular Energy Allocation Approach - Shang, Yueyong; Wang, Xinghuo; Chang, Xueqing; Sokolova, Inna M.; Wei, Shuaishuai; Liu, Wei; Fang, James K. H.; Hu, Menghong; Huang, Wei; Wang, Youji (Frontiers in Marine Science, 2021)
Marine microplastics pollution is a major environmental concern in marine ecosystems worldwide, yet the biological impacts of microplastics on the coastal biota are not yet fully understood. We investigated the impact of suspended microplastics on the energy budget of the mussels Mytilus coruscus using the Cellular Energy Allocation (CEA) approach. The mussels were exposed to control conditions (no microplastics) or to one of the three concentrations of 2 μm polystyrene microspheres (10, 104, and 106 particles/L) for 14 days, followed by 7 days of recovery. Exposure to high concentrations of microplastics (104 or 106 particles/L) increased cellular energy demand (measured as the activity of the mitochondrial electron transport system, ETS) and depleted cellular energy stores (carbohydrates, lipids and proteins) in the mussels whereas exposure to 10 particles/L had no effect. Carbohydrate levels decreased already after 7 days of microplastics exposure and were restored after 7 days of recovery. In contrast, the tissue levels of lipids and proteins declined more slowly (after 14 days of exposure) and did not fully recover after 7 days following the removal of microplastics. Therefore, the total energy content and the CEA declined after 7-14 days of exposure to high microplastics concentrations, and remained suppressed during 7 days of subsequent recovery. These findings demonstrate a negative impact of microplastics on energy metabolism at the cellular level that cannot be restored during a short time recovery. Given a close link of CEA with the organismal energy balance, suppression of CEA by microplastics exposure suggests that bioenergetics disturbances might lead to decreases in growth and productivity of mussels’ populations in environments with heavy microplastics loads.